Diversity of carbapenemases in clinical isolates: The emergence of blaVIM-5 in Bangladesh. Issue 6 (June 2019) - Rakhi, Nadira Naznin; Alam, A.S.M. Rubayet Ul; Sultana, Munawar; Rahaman, Md. Mizanur; Hossain, M. Anwar
Abstract: Global emergence and dissemination of carbapenemases are clinically threatening, notably in countries with endemic bla NDM . To analyze the extent of carbapenemases in Bangladesh, 71 isolates were collected from 7 different clinical sources: wound swab (n = 38), pus (n = 13), urine (n = 9), blood (n = 4), tracheal aspirate (n = 3), pleural fluid (n = 1) and vaginal swab (n = 3) from Dhaka Medical College Hospital, Bangladesh. Among the isolates, 25 were resistant to at least one of the three carbapenems (imipenem, meropenem and doripenem), including 15 being resistant to all. These resistant isolates were identified as Pseudomonas aeruginosa, Acinetobacter baumannii, Klebsiella pneumoniae, P. hibiscicola, Proteus mirabilis, Providencia stuartii and Citrobacter sedlakii. Carbapenemase detection among these 25 isolates varied in individual phenotypic assays (83% in Modified Hodge Test, 50% in Combined Disk Test for Metallo-β-lactamase prediction) as compared with the genotypes observed (96% prevalence of various carbapenemases including bla OXA-1, 48, bla NDM-1, 5, bla VIM-2, 5 ). bla OXA-48 was the most prevalent gene (84%) followed by bla NDM (72%). Coexistence of multiple gene combination such as bla NDM + bla OXA-48 + bla OXA-1 was prevalent (48%). Harborage of bla VIM-5 (n = 1) was characterized for the first time, while bla NDM-5 (n = 5) was reported contemporarily with a recent study in Bangladesh. Presence of plasmids (64%) and integron class 1 (100%) signifies the transferable potential of resistant traits. The emergence of such new variants along with the presence of the mobile genetic elements demands strict surveillance and combating strategies.